Futuretalk: one small step towards a Chronolinguistics - Stockwell, Peter (2000)
In the area of linguistics and language teaching, science fiction is useful in very many ways. An obvious way is that it sets up many complex and rich worlds and outlines the sorts of adjustments that language must make in those contexts. It thus draws a strong link between language and context; it shows how the construction of reality is largely a matter of language; and it speculates on where we are linguistically heading. It is a useful mirror on language development.